MECHANISMS TO ENHANCE THE COMPETITIVENESS OF STATE-OWNED CORPORATIONS - Pavel V. Trifonov (Статистика и экономика, 2016)
The article is devoted to the developmentof mechanisms to increase the competitiveness of the integrated corporate structureswith state participation. Special attentionis paid to the key factors in the evaluationof competitiveness. The article presents a comparative analysis of the competitivenessindex of major international corporations andthe Russian state corporations engaged instrategic sectors. The preconditions for the formation mechanisms of competitivenessfor corporations are provided. Getting acompetitive advantage in the internationalarena is possible through effective interaction between the state and integrated corporate structures in access to scientiﬁ c and technical progress and the development ofinnovative potential.